2020
DOI: 10.1128/iai.00305-20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CARD9 Deficiency on Neutrophil-Mediated Host Defense against Pulmonary Infection with Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is a major causative bacterium of community-acquired pneumonia. Dectin-2, one of the C-type lectin receptors (CLRs), was previously reported to play a pivotal role in host defense against pneumococcal infection through regulating phagocytosis by neutrophils while not being involved in neutrophil accumulation. In the present study, to elucidate the possible contribution of other CLRs to neutrophil accumulation, we examined the role of CARD9, a common adaptor molecule for signal transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Previous publications have revealed that Dectin-2 served as a critical regulator in host immunity against Streptococcus pneumoniae infection by affecting phagocytosis of neutrophils but excluding the recruitment of neutrophils (McGreal et al, 2006 ; Akahori et al, 2016 ). At present, Ishizuka et al ( 2020 ) found that CARD9 KO mice other than dectin-2 KO mice showed impaired neutrophil recruitment and decreased inflammatory cytokine and chemokine production compared to respective control mice. They indicated that CARD9-mediated signaling was indispensable in anti- pneumococcal immunity through modulating neutrophil function and cytokine production, in which both neutrophil phagocytosis and neutrophil accumulation required the participation of CARD9.…”
Section: Bacteriamentioning
confidence: 94%
“…Previous publications have revealed that Dectin-2 served as a critical regulator in host immunity against Streptococcus pneumoniae infection by affecting phagocytosis of neutrophils but excluding the recruitment of neutrophils (McGreal et al, 2006 ; Akahori et al, 2016 ). At present, Ishizuka et al ( 2020 ) found that CARD9 KO mice other than dectin-2 KO mice showed impaired neutrophil recruitment and decreased inflammatory cytokine and chemokine production compared to respective control mice. They indicated that CARD9-mediated signaling was indispensable in anti- pneumococcal immunity through modulating neutrophil function and cytokine production, in which both neutrophil phagocytosis and neutrophil accumulation required the participation of CARD9.…”
Section: Bacteriamentioning
confidence: 94%
“…Mice were sacrificed at various timepoints after infection. Bronchoalveolar lavage fluids (BALFs) were prepared as previously described 34 , 35 . After the BALFs were collected, lung homogenates were prepared as previously described 11 , 30 33 .…”
Section: Methodsmentioning
confidence: 99%
“…CARD9 is involved in immune signaling linked to bacterial infections through TLRs (TLR2 and TLR4) and NLRs (NOD1 and NOD2) [ 5 ]. Additionally, CLR signaling contributes to antibacterial immunity [ 52 , 53 , 54 ]. NODs collaborate with CARD9 to facilitate the recognition of bacterial peptidoglycan monosaccharide units known as muramyl dipeptide (MDP).…”
Section: Effects Of Card9 On the Immune Response To Bacterial Infectionsmentioning
confidence: 99%
“…CARD9-deficient mice showed reduced specific-immune cell infiltration in the lungs compared to the wild type in response to pneumococcal infection; specifically, the number of neutrophils was significantly reduced compared to the wild type, but the number of macrophages was not altered [ 54 ]. This is because the cytokines and chemokines involved in neutrophil recruitment are reduced by CARD9 deficiency [ 54 ].…”
Section: Effects Of Card9 On the Immune Response To Bacterial Infectionsmentioning
confidence: 99%